Evaluation of Solid Waste Management of Municipalities in the Inter-municipal Solid Waste Consortium of Oeste Paulista (CIRSOP) - Pestana , Laura de Oliveira Battistini; Ventura, Katia Sakihama (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The inter-municipal consortium was proposed as one of the initiatives of the National Solid Waste Policy as it allows the deployment of infrastructure on a regional scale, reducing operational costs and increasing the quality of life of the population served by these services. In this sense, the main objective of the work was to evaluate the management of solid waste in sanitary landfill, selective collection, waste composting and reverse logistics for the municipalities of the Inter-municipal Solid Waste Consortium of Oeste Paulista (CIRSOP). The method consisted of the organization of the theoretical framework, the selection of the study object and the evaluation of the initiatives established by the SAGReS software, consisting of an electronic spreadsheet prepared from monitoring variables. Of the total of 10 municipalities in CIRSOP, 50% allocate their waste to sanitary landfill. In addition, there is a lack of control of working conditions in selective collection cooperatives, lack of environmentally adequate destination for organic waste through composting, lack of control of parameters for reverse logistics and the need to disseminate information in online media, as these are not fully available or updated. The study identified that the biggest challenges of CIRSOP are the aspects involving composting, reverse logistics and landfill.